GAMBARAN SIKAP DAN TINDAKAN IBU DALAM MENCEGAH COVID-19 PADA ANAK BALITA - Rizalti, Rezky; Arneliwati, Arneliwati; Indriati, Ganis (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022DO - 10.24843/coping.2022.v10.i05.p03, 2022)
Coronavirus Disease-2019  (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2  (SARS-CoV 2). The spread of COVID-19 is so fast that it is easy to infect toddlers. Mothers have a vital role in protecting their children from COVID-19. This study aims to determine the description of mothers' attitudes and actions in preventing COVID-19 in toddlers. The research design is descriptive quantitative research with  a cross-sectional  approach .  Data was collected using a questionnaire consisting of 17 statements about mothers' attitudes and actions in preventing COVID-19 in toddlers and given to 173 respondents with toddlers aged 12 - 59 months in North Tangkerang, Pekanbaru. The data analysis using a simple descriptive presented in the frequency distribution table. The results showed that the mother's attitude was in the positive category with a total of 89 respondents (51,4%), and the mother's action was in the good category with a total of 100 respondents (57,8%). It can be concluded that mothers with toddlers aged 12 - 59 months in North Tangkerang, Pekanbaru have positive attitudes and good actions in preventing COVID-19.